Social protection to Childhood towards the Covid-19 pandemic. Policy and institutional implications of the government response from Mexico City (2021)
The purpose of the case study is to analyze the response of the government of Mexico City to the crisis derived from COVID-19 and in particular the way it has affected the social protection of children in Mexico during the first months of the pandemic. Regulatory institutional design of social protection for children in Mexico, and particularly in Mexico City, is analyzed, as well as the activities of the government of Mexico City to reduce the impact of the crisis on children. Theoretically and methodologically the article follows the qualitative case study strategy supported by the literature on crisis management and institutional analysis. One of the main findings is found in the existence of regulatory mechanisms and programs from the international to the local level, as well as the weaknesses in the social protection mechanisms against COVID-19; Furthermore, the practical implications are found both in the generation of new lines of research and in the coordination mechanisms between the levels of government.